1996
DOI: 10.1101/gad.10.16.2003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of hedgehog target genes in Drosophila is mediated directly by the cubitus interruptus protein, a member of the GLI family of zinc finger DNA-binding proteins.

Abstract: Members of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
250
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(260 citation statements)
references
References 65 publications
7
250
0
1
Order By: Relevance
“…Expression changes in IGF2, BF-2, Amh and SFRP-2 in response to Gli1 transfection provide a further level of evidence for these genes as bona fide downstream targets of Shh signalling. DNA binding studies have indicated that human Gli1 binds the nine base pair consensus sequence GACCACCCA (Kinzler and Vogelstein, 1990), with functional assays confirming a number of closely related sequences are also bound by Gli proteins in a range of species (Alexandre et al, 1996;Sasaki et al, 1997;Gustafsson et al, 2002;Yoon et al, 2002). Analysis of available upstream promoter sequence obtained from the Celera mouse database showed a number of putative and known Gli binding motifs to be present in each of the four Shh target genes shown to be regulated by Gli1.…”
Section: Discussionmentioning
confidence: 99%
“…Expression changes in IGF2, BF-2, Amh and SFRP-2 in response to Gli1 transfection provide a further level of evidence for these genes as bona fide downstream targets of Shh signalling. DNA binding studies have indicated that human Gli1 binds the nine base pair consensus sequence GACCACCCA (Kinzler and Vogelstein, 1990), with functional assays confirming a number of closely related sequences are also bound by Gli proteins in a range of species (Alexandre et al, 1996;Sasaki et al, 1997;Gustafsson et al, 2002;Yoon et al, 2002). Analysis of available upstream promoter sequence obtained from the Celera mouse database showed a number of putative and known Gli binding motifs to be present in each of the four Shh target genes shown to be regulated by Gli1.…”
Section: Discussionmentioning
confidence: 99%
“…Using retroviral expression vectors to derive pure polyclonal cell lines, we used northern blot to assess the state of signaling via this pathway. Figure 1a demonstrates that EWS/FLI induces augmented levels of GLI1 and Figure 1b shows that the direct target of GLI1, PATCHED1 (Alexandre et al, 1996;Marigo et al, 1996;Hepker et al, 1997), is also upregulated. Figure 1c demonstrates that levels of GLI1 protein correlate with this transcriptional upregulation.…”
Section: Ews/fli1 Enhances Gli1 Expression In Nih3t3 Cellsmentioning
confidence: 99%
“…The transcription factor Ci is the most down-stream component of the Hh signaling pathway, and can function as either a transcriptional activator or repressor in response to varying levels of Hh stimulation [32,[52][53][54][55]. In the absence of Hh, the repressor form of Ci, Ci 75 , holds target genes in a repressed state.…”
Section: Cubitus Interruptusmentioning
confidence: 99%